Parmales in sediments of Prydz Bay, East Antarctica: a new biofacies and paleoenvironmental indicator of cold water deposition? - Franklin, DC; Marchant, HJ (Micropaleontology, 1995)
Siliceous wall plates of two species of Parmales are present in varying abundance in the surficial and downcore sediments of Prydz Bay. These organisms have a dramatically higher abundance and greater species diversity in polar and sub-polarenvironments than is seen in temperate and tropical waters. Based on the finding of abundant and well-preserved walls of these organisms in Antarctic sediments, it is suggest that they represent a useful biofacies and paleoenvironmental marker for deposition from cold water, and a potentially new biostratigraphic tool. -Authors